Combined transoral and endoscopic approach for cervical spine tumor resection - Zhou, Jun (Medicine (Baltimore), 2019)
This study aimed to explore the feasibility and clinical effectiveness of a combined transoral and endoscopic approach for the removal of benign cervical spine tumors. First, we obtained detailed anatomical measurements of the atlantoaxial joint from 20 fresh cadaveric specimens and performed simulated surgeries with the combined transoral and endoscopic approach on 10 cadaveric specimens. Then, we applied the combined approach for the resection of benign cervical spine tumors in 8 patients at our hospital from October 2013 to October 2015. All patients underwent enhanced axial, coronal, and sagittal computed tomography (CT) examination before and after surgery. Preoperative 3-dimensional (3D) reconstruction and printing models were used in 5 cases. On the basis of CT measurements of fresh cadaveric atlantoaxial anatomy and practical experiences from simulated surgeries on the cadaveric specimens with latex perfusion, cervical tumors were completely removed from 8 patients without complications. The average surgery time was 73 minutes, and the average intraoperative bleeding volume was 34 mL. The average hospital stay was 6.5 days. The average NRS score of patients was 2.25 points at 3 days postoperation. At the 12-month postoperative follow-up, the atlantoaxial vertebral bone had been largely repaired, and no recurrence was observed by cervical CT examination. The combined transoral and endoscopic approach could be used safely and effectively to excise cervical spine tumors with substantial advantages, including direct surgical access, relatively simple operation, short operative time, quick postoperative recovery, a reliable curative effect, and few complications.